Enhancing Students’ Science Achievement through Jigsaw II Strategy - James L. Tabiolo; Danilo Jr. Villar Rogayan (Journal of Science Learning, 2019)
The Science education curriculum in the Philippines has shifted from inputs-based to outcomes-based education putting the learners at the core of the instruction. Hence, educators continue to innovate ways on how to engage the learners into a relevant and responsive science instruction. Further, the implementation of the K to 12 curriculum brings a paradigm shift in education in terms of pedagogy, assessment and outcomes. This within group quasi-experimental research attempts to test the effects of Jigsaw II strategy on the students’ science achievement. A total of 51 Grade 9 students in a government-run secondary school in Zambales, Philippines participated in the study. Results revealed that the class improved from “approaching proficiency” to “proficient” level in their science achievement after the implementation of the strategy. It was found out that Jigsaw II strategy had a significant effect on the science achievement of the learners. The study recommends the use of the instructional strategy in enhancing students’ achievement. The strategy may be applied in other science topics to further see its effectiveness. This paper likewise contributes to the literature on the effectiveness of Jigsaw II learning strategy in the science teaching in the Philippine context.